Health-economic evaluation of psychological interventions for depression prevention: Systematic review. (August 2021) - Conejo-Cerón, Sonia; Lokkerbol, Joran; Moreno-Peral, Patricia; Wijnen, Ben; Fernández, Anna; Mendive, Juan M.; Smit, Filip; Bellón, Juan Ángel
Abstract: Psychological interventions have been proven to be effective to prevent depression, however, little is known on the cost-effectiveness of psychological interventions for the prevention of depression in various populations. A systematic review was conducted using PubMed, PsycINFO, Web of Science, Embase, Cochrane Central Register of Controlled Trials, Econlit, NHS Economic Evaluations Database, NHS Health Technology Assessment and OpenGrey up to January 2021. Only health-economic evaluations based on randomized controlled trials of psychological interventions to prevent depression were included. Independent evaluators selected studies, extracted data and assessed the quality using the Consensus on Health Economic Criteria and the Cochrane Risk of Bias Tool. Twelve trial-based economic evaluations including 5929 participants from six different countries met the inclusion criteria. Overall, the quality of most economic evaluations was considered good, but some studies have some risk of bias. Setting the willingness-to-pay upper limit to US40, 000 (2018 prices) for gaining one quality adjusted life year (QALY), eight psychological preventive interventions were likely to be cost-effective compared to care as usual. The likelihood of preventive psychological interventions being more cost-effective than care as usual looks promising, but more economic evaluations are needed to bridge the many gaps that remain in the evidence-base. Ethics: As this systematic review is based on published data, approval from the local ethics committee was not required. Highlights: Twelve trial-based health-economic evaluations to prevent depression are presented Nine of these 12 studies were CUAs of which 6 were cost-effective The remaining 3 studies were CEAs of which 2 were cost-effective Psychological interventions have the potential to be cost-effective More economic evaluations should be conducted for priority setting